Pitaya quality during refrigerated storage - Brunini, M. A. [UNESP]; Cardoso, S. S.; Guimarães, J. E.R.; Oliveira, A. L.; Pereira, M.; Kanesiro, L. A.; Kanesiro, J. C.; Lopes, M. C. [UNESP] (International Society for Horticultural Science (ISHS), 2017)
The objective of this study was to evaluate the quality and shelf life of pitaya fruits, stored under an ambient temperature (21-27°C with 44-63% RH) and at a low temperature (12±1°C, with 85-90% of RH). The quality of the fruit was monitored during the storage, using the parameters: weight loss, the external coloration, the titratable acidity, the amount of soluble solids, amount of vitamin C, the enzymatic activity of pectin methyl esterase, the respiration rate and the sensory acceptability (flavor, coloration, texture, global impression). Through the results it may be concluded that the shelf life of pitaya could be extended for 18 days by storing at refrigerated temperature (12±1°C) compared with those stored at room temperature. The use of refrigerated temperature (12±1°C) however, increased the loss in fresh weight and enzymatic activity of pectin methyl esterase (PME), which is associated with the softening of fruits. The quality of fruit was influenced by the storage temperature and storage time, however storage of fruits at the refrigerated temperature (12±1°C) showed small change in the fruit quality. In general, it may be concluded that the refrigerated temperature (12±1°C) was the best to maintain pitaya fruit quality.
Keywords: Ascorbic acid; Hylocereus undatus (Haw.); Soluble solid; Titrable acidity; Weight loss